The Florida project. - Baker, Sean, 1971-; Dafoe, Willem; Prince, Brooklynn, 2010-; Vinaite, Bria, 1993-; Cotto, Valeria; Rivera, Christopher, 2007 or 2008-; Jones, Caleb Landry (Santa Monica, CA : Lions Gate Entertainment, 2018)
Set over one summer, the film follows precocious six year old Moonee as she courts mischief and adventure with her ragtag playmates and bonds with her rebellious but caring mother, all while living in the shadows of Disney World.
Originally released as a motion picture in 2017.
Special features: Under the rainbow: making The Florida project; bloopers and outtakes; cast and crew interviews.
Produced by Sean Baker, Chris Bergoch, Shih-Ching Tsou, Andrew Duncan, Alex Saks, Kevin Chinoy, Francesca Silvestri ; written by Sean Baker & Chris Bergoch ; directed by Sean Baker.
MPAA rating: R; language throughout, disturbing behavior, sexual references and some drug material.
DVD, region 1, widescreen (2.40:1) presentation; 5.1 Dolby digital.
English dialogue; optional Spanish subtitles; English subtitles for the deaf and hard of hearing (SDH).
Keywords: Drama films